Correction of measurements results on dynamic modes of flight - Папченко, О.М. (Proceedings of National Aviation University (archive), 2005)
Questions of increase accuracy of measurements are considered at registration of parameters on dynamic modes of flight any flying device on the basis of the analysis and research dynamic errors of gauges for its account during the any moments of time.